2016
DOI: 10.12659/pjr.896312
|View full text |Cite
|
Sign up to set email alerts
|

Intramammary Findings on CT of the Chest – a Review of Normal Anatomy and Possible Findings

Abstract: SummaryComputed tomography (CT) is a frequently performed examination in women of all ages. In all thoracic CT examinations of the chest at least parts of the breasts are included. Therefore incidental breast pathology may be observed. It has been suggested that one out of 250 women undergoing chest CT will show a malignant incidental breast lesion. Given the high number of performed chest CT examinations, this contributes to a significant number of malignancies. In this review, after a brief discussion of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 17 publications
(17 reference statements)
0
12
0
Order By: Relevance
“…There was no special preparation on the MSCT Thorax examination of breast cancer cases but patients were asked to change the clothes that had been provided. During the examination, the patient does not use metal tools that may interfere with the radiograph image (Gossner, 2016). According to (Bhalla et al, 2019) examinations that use contrast media should use fasting 6 hours before the examination is carried out and laboratory checks (ureum cratinin within normal limits), this is the same as explaining routine examination techniques according to (Wijokongko et al , 2016) which requires laboratory examination (the latest results of cratinin ureum within normal limits i.e.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…There was no special preparation on the MSCT Thorax examination of breast cancer cases but patients were asked to change the clothes that had been provided. During the examination, the patient does not use metal tools that may interfere with the radiograph image (Gossner, 2016). According to (Bhalla et al, 2019) examinations that use contrast media should use fasting 6 hours before the examination is carried out and laboratory checks (ureum cratinin within normal limits), this is the same as explaining routine examination techniques according to (Wijokongko et al , 2016) which requires laboratory examination (the latest results of cratinin ureum within normal limits i.e.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, setting parameters, it is certain that the upper limit of the pulmonary Apex and the lower limit of the diaphragm enter the examination area and then the scanning process continues. The patient's position according to journal 2 (Gossner, 2016) is that the patient is positioned as comfortable as possible, with the body position in the middle of the examination table, both hands above the head, the upper limit of the pulmonary apex and the inferior lower limit of the hepar. The patient is instructed to remain silent during the examination and immediately signal if experiencing discomfort, so that the officer will immediately stop the examination.…”
Section: Inspection Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…Thirdly, in contrast to other screening studies, the number of incidental breast lesions reported in our dataset is relatively high; 8 out of 232 participants (3%), versus 1% mentioned in literature. [34] This could have been caused by the fact that our cohort consisted of women with a younger age when compared to the other screening studies, with densely glandular breast tissue that might have been reported as suspicious breast masses. Furthermore, CT without intravenous contrast makes it more difficult to distinguish lesions from dense glandular tissue.…”
Section: Discussion (1158)mentioning
confidence: 96%
“…Therefore solid lesion needs further workup with ultrasound and mammography. Exceptions are lesions with coarse central calcifications, which are pathognomic for involuted fibroadenomas 6 . It has to be noted that microcalcifications cannot be seen with CT. 6 …”
Section: Cancermentioning
confidence: 99%